Comparison of action performances and outcome between winners and losers in young female silat tempur matches (Revista de Artes Marciales Asiáticas, 2019)
Silat (a.k.a. gayung) tempur is a combat sports competition introduced to provide early preparation for the beginners to master the basic techniques of silat before they shift to silat olahraga (advanced level competition). The purpose of this study was to compare the performance of actions and outcome during action time between winners and losers in national silat tempur competition. The notational analysis focused on five different types of action categories in silat tempur; kick, punch, topple, block and catch. The action categories were divided into three outcomes; Hit Target (HT), Hit Elsewhere (HE) and Missing Opponent (MO). The researchers observed 19 female silat matches (each with three round games) aged 14 to 17-year-old. The observations were made through series of videos. Matched Paired t-test was used to analyse each action performances and outcome between winners and losers. Results showed that the winners performed more actions than the losers (p < 0.05). The winners frequently used more kicks to attack their opponents (p < 0.05). However, there were similar performance between winners and losers in punch, block, topple and catch categories (all actions, p > 0.05). The winners performed more successful actions (HT) than the losers (p < 0.05), particularly on kicks and blocks (both actions, p < 0.05). The losers significantly missed (MO) more catch actions than the winners (p < 0.05). The author concluded that kicks were the main actions that both exponents used during silat matches, with the winners performing more successful actions than the losers.